Legal Regulation of Quarantine A Comparative Analytical Study - Bamo Parez Khan al-Dalwi; Ismail Namq Hussein (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
This research article made comparison among the laws of Iraq, the Kurdistan Region, laws of the United Arab Emirates, and the Hashemite Kingdom of Jordan. The research focused on the provisions of quarantine. And, it was found that these laws took the doctrine of conciseness and abbreviation in the declaration of judgments, which resulted in legislative deficiencies in relation to important aspects of quarantine, such as the rights and obligations of the quarantined, as well as the liability entailed by the breach of the provisions of the quarantine, in addition to that the comparative laws did not distinguish between the provisions of quarantine and its procedures at the regular time and its provisions at the time of the epidemic or pandemic, as it only regulated the provisions of individual quarantine, and did not address the provisions of collective quarantine. Therefore, we suggested that a new public health law be enacted in Iraq, in which the provisions of quarantine will be comprehensively detailed in a chapter, provided that this regulation is based on balance and weighting between public health requirements and the requirements of human dignity.